The Role of Electronic Media in the Political Process (2011-2019): Wasit University as a Model - Muntadher Mohammed Jedi, Asst. Lect. (lark, 2025)
Modern media is one of the most essential necessities of our contemporary life and one of the most important sources of information about the world around us, serving as a link between all institutions, whether religious or political. The first chapter of the research contains the methodological framework, which includes the research problem, examining the elite status of media and the effectiveness of media messages under various conditions and changes. The importance of this study lies in identifying the key points that politicians seek in the media and highlighting their necessity and priority. The aim of the study is to understand the role that media plays in politics and to reveal the reasons politicians resort to media.A descriptive method was used in the study for analysis purposes. This chapter also reviews previous studies that dealt with electronic media and politics. The second chapter provides a theoretical framework addressing the functions of electronic media in political systems, covering its concepts, types, and functions. The third chapter is practical, presenting the study procedures and explaining the steps taken by the researcher, such as creating a questionnaire, setting its metrics, and selecting a sample from Wasit University, distributing it to 220 respondents. The study yielded several findings, including that electronic media has the highest rate of publishing political content. The researcher concluded that electronic media has contributed to spreading political awareness and is characterized by its speed in conveying news and political events and changes.The researcher also recommends enacting a law to limit the phenomenon of electronic blackmail that distorts public, political, or religious figures. Legitimate public issues published on electronic media platforms should be taken into consideration and addressed swiftly in Iraq.
Keywords: : role, electronic media, political process, Wasit University